2017
DOI: 10.1186/s12884-017-1604-1
|View full text |Cite
|
Sign up to set email alerts
|

“I am a person but I am not a person”: experiences of women living with obstetric fistula in the central region of Malawi

Abstract: BackgroundThe consequences of living with obstetric fistula are multifaceted and very devastating for women, especially those living in poor resource settings. Due to uncontrollable leakages of urine and/or feces, the condition leaves women with peeling of skin on their private parts, and the wetness and smell subject them to stigmatization, ridicule, shame and social isolation. We sought to gain a deeper understanding of lived experiences of women with obstetric fistula in Malawi, in order to recommend interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 29 publications
(42 reference statements)
3
61
0
Order By: Relevance
“…Having a negative attitude and feeling worthless bother them. The combination of the constant presence of problem and loss of role leads to feelings of worthlessness [30], and women lose selfconfidence [15], and the combination of these negative attitudes, physical symptoms, and the reactions of relatives result in these consequences in these patients. These consequences manifest in the form of mental crises, sleep disturbances and social isolation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having a negative attitude and feeling worthless bother them. The combination of the constant presence of problem and loss of role leads to feelings of worthlessness [30], and women lose selfconfidence [15], and the combination of these negative attitudes, physical symptoms, and the reactions of relatives result in these consequences in these patients. These consequences manifest in the form of mental crises, sleep disturbances and social isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, depression and psychological complications are the consequence of the disease [8,10,12], and the problems somewhat persist even with this complication is repaired [13,14]. The obstetric fistulas have multiple effects as well as medical and psychosocial outcomes, and urinary and fecal incontinence makes it difficult to maintain proper health for individuals and to perform routine social and occupational activities [15]. Lack of awareness and knowledge of the cause and treatment of fistulas by family and community members may lead to misconceptions that may then expose these women to greater stress and stigma, making their overall quality of life very poor and unbearable [4, 14,16,17].…”
mentioning
confidence: 99%
“…Studies mention of witchcraft, curses, and misfortunes as the perceived causes of fistula. 2,10 A participant in a study done in Uganda in 2019 stated that she was despised by her in-laws who blamed her for extending her curse to their family. 3 In another study in Malawi, findings indicated that a patient perceived the cause of obstetric fistula as either witchcraft or the devil at work.…”
mentioning
confidence: 99%
“…Another one believed it was magical powers. 10 Considering these beliefs and anticipated stigma, patients tend to give up on social life in fear of embarrassment. Besides, stress incontinence is also common among successfully repaired patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation